International Migration: Driver of Political and Social Change? - Michele Tuccio; Jackline Wahba; Bachir Hamdouch (Institute for the Study of Labor (IZA), 2016)
This paper focuses on the impact of international migration on the transfer of political and social norms. Exploiting recent and unique data on Morocco, it explores whether households with return and current migrants bear different political preferences and behaviours than non-migrant families. Once controlling for the double selection into emigration and return migration, findings suggest that having a returnee in the household increases the demand for political and social change, driven by returnees mostly from Western European countries, who have been exposed to more democratic norms at destination. However, we find a negative impact of having a current migrant on the willingness to change of the left-behind household, driven by migrants to non-West countries, where the quality of political and social institutions are lower. Our results are robust to also controlling for destination selectivity. Finally, findings suggest that migration not only affect political attitudes but also actual behaviour: regions with higher returnee shares have had greater participation rates in the 2011 political elections.
Keywords: D72; F22; O15; O55; 330; international migration; political change; transfer of norms; Morocco